2017
DOI: 10.1021/acs.joc.6b02466
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Role of Glycol Chain Lengths in π-Donor–Acceptor [2]Pseudorotaxanes Based on Monopyrrolo-Tetrathiafulvalene and Cyclobis(paraquat-p-phenylene)

Abstract: We have investigated and quantified the role that the glycol chain length has on the strength of the noncovalent bonding interactions taking place between cyclobis(paraquat-p-phenylene) (CBPQT) and five different monopyrrolo-tetrathiafulvalene (MPTTF) derivatives that only differ in the length of the N-substituted glycol chain. The MPTTF derivatives were used to form [2]pseudorotaxanes by mixing them with CBPQT. The binding constants (K) associated with the complexation process leading to the formation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…To account for solvation an implicit Poisson‐Boltzmann solvation model was used to simulate a solution of MeCN ( R 0 = 2.2 Å; ε = 37.5). This combination of functional, basis set, and solvent model has previously been used to describe the structural and energetic properties of related superstructures and mechanically interlocked molecules , , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for solvation an implicit Poisson‐Boltzmann solvation model was used to simulate a solution of MeCN ( R 0 = 2.2 Å; ε = 37.5). This combination of functional, basis set, and solvent model has previously been used to describe the structural and energetic properties of related superstructures and mechanically interlocked molecules , , …”
Section: Resultsmentioning
confidence: 99%
“…It has been concluded[9a], [12b], that the most electron rich (i.e., the stronger π‐electron donors) form more stable host–guest complexes with the CBPQT 4+ ring. Most recently, it has been demonstrated that ethylene glycols can also assist the complexation process[12b], between TTF derivatives and CBPQT 4+ by forming tertiary (3°) superstructures . Consequently, several catenanes and rotaxanes incorporating TTF derivatives and CBPQT 4+ have been reported in the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary structures for geometry optimization have been generated by merging CBPQT 4+ from previous work and a DHA crystal structure [CCDC 792112] followed by dynamics calculations in Maestro 10 release 2016–2 Schrödinger using MMFFS as the force field, as structure search method to find 1000 superstructures. From these minimized superstructures, 10 were chosen for optimization at higher level of theory which was done stepwise with HF/STO‐3G, HF/6‐31G, HF/6‐31G* and finally in HF/6‐31+G* using a MeCN PCM solvent model using quadratically convergent SCF procedure .…”
Section: Methodsmentioning
confidence: 99%
“…In later reports, differently substituted TTF derivatives as for example 2 , 4 , and 5 have been investigated towards their binding to host 3 [ 24 , 59 63 ]. π-Electron-rich TTFs form significantly stronger donor–acceptor complexes as π-electron-poor TTFs.…”
Section: Reviewmentioning
confidence: 99%
“…π-Electron-rich TTFs form significantly stronger donor–acceptor complexes as π-electron-poor TTFs. However, also the type of substituent on the TTF moiety plays a role in terms of weak secondary binding interactions such as hydrogen bonds [ 63 ]. For example TTF 5 which is substituted by ethylene glycol chains displays a high association constant of K a = 50,000 M −1 in acetonitrile.…”
Section: Reviewmentioning
confidence: 99%